Menyemai Nalar Kebhinnekaan dalam Mewujudkan Pendidikan Multikultural - Anas, Mohammad (Universitas Negeri Malang, 2019)
This paper discusses the multiculturalism idea in the philosophy of Bhinneka Tunggal Ika and nationalism, and multicultural education in the Indonesian context. The article used a qualitative approach to Library Research. Library research carried out is to collect multiculturalism opinions of experts, both the great figures of the history of the Indonesian nation and academics who are concerned about the value of multiculturalism. The results obtained are (1) the concept of Indonesian unity in the philosophy of Bhinneka Tunggal Ika and nationalism is called integrative-pluralist, which is constitutionally realized in the articles of the 1945 Constitution, (2) multicultural education in the Indonesian context must not be ahistorical and able to produce graduates who have the skills to live in a multicultural society so that national integration is maintained.